Implementation of Cognitive Theory in Developing Measurement Learning Multimedia for Deaf Students - Suarsana, I Made; Sudatha, I Gde Wawan; Mahayukti, Gusti Ayu; Suandana, I Wayan Edy Ari; Suharta, I Gusti Putu (Universitas Pendidikan Ganesha, 2021)
The implementation of cognitive theory in multimedia development for deaf students (students with visual channels only) would be re-examined for its effectiveness. This study aimed to develop mathematics-learning multimedia based on cognitive theory for deaf students on